Solving exponential equations with a common base problem in the picture!
![Solving exponential equations with a common base problem in the picture class=](https://us-static.z-dn.net/files/de5/899e6916f10745f2a3cd2ab5be3434e5.png)
Given:
The given expression is [tex]18^{x^{2}+4 x+4}=18^{9 x+18}[/tex]
We need to determine the solution of the given expression.
Solution:
Let us solve the exponential equations with common base.
Applying the rule, if [tex]a^{f(x)}=a^{g(x)}[/tex] then [tex]f(x)=g(x)[/tex]
Thus, we have;
[tex]x^{2}+4 x+4=9 x+18[/tex]
Subtracting both sides of the equation by 9x, we get;
[tex]x^{2}-5 x+4=18[/tex]
Subtracting both sides of the equation by 18, we have;
[tex]x^{2}-5 x-14=0[/tex]
Factoring the equation, we get;
[tex]x^2-7x+2x-14=0[/tex]
Grouping the terms, we have;
[tex](x^2-7x)+(2x-14)=0[/tex]
Taking out the common term from both the groups, we get;
[tex]x(x-7)+2(x-7)=0[/tex]
Factoring out the common term (x - 7), we get;
[tex](x+2)(x-7)=0[/tex]
[tex]x+2=0 \ and \ x-7=0[/tex]
[tex]x=-2 \ and \ x=7[/tex]
Thus, the solution of the exponential equations is x = -2 and x = 7.
Hence, Option C is the correct answer.